PENGARUH GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA PERAWAT DI RUANG RAWAT INAP A RSUP DR. SOERADJI TIRTONEGORO KLATEN - Qurratul 'Aini; Herianto Sosilo (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2014)
Inpatient services of RSUP Dr. Soeradji Tirtonegoro Klaten is a complex set of services and giving major contribution in determining the quality of service. Nurses play an important role as the spearhead of the longest and energy dealing with patients. Nurses activities reflect the image of the hospital, nurses' performance is inseparable from leadership and job satisfaction. The purpose of research is knowing the influence the effect of leadership style and job satisfaction toward performance. The type of research is quantitative research with a cross sectional design. Independent variable leadership style and job satisfaction, the dependent variable is the performance of nurses. The registered nurse population as a civil servant ( PNS ), amounting to 75 people, collecting sampling techniques total sampling. Analysis techniques of Multiple linear regression. The results is Significance value of leadership style of 0.022 (Sig.< 0,05) and job satisfaction 0.132 (Sig.> 0,05). Test results of F 15.779 with significance level of 0.000. Adjusted R2 coefficient of 28.5 %. The conclusion is 1) leadership style effect a significant toward the nurses performance, 2) job satisfaction variable does not affect the nurses performance, and 3) Leadership Style And Job Satisfaction simultaneously influence toward the nurse performance of inpatient ard A RSUP Dr. Soeradji Tirtonegoro Klaten.